Lamb mortality in an organized farm: Cause and control - DEY, S; DWIVEDI, S K; VARSHNEY, J P (The Indian Journal of Animal Sciences, 2014)
An unexplained mortality with signs of diarrhoea recumbency and ataxia in lambs in an organized farm in Northern India was investigated during June 1997. The ailment was characterized by afebrile sickness with loose faeces, posterior ataxia. pale conjunctive, dullness, refractary appetite, inco-ordinated gait, weakness and recumbency. Faecal examination ruled out parasitic diarrhoea. Haemogram revealed anaemia Mean blood micromineral content were estimated as 2.16±0.14, 38±0.08, 0.028±0.02, 0.32±0.06 and 0.011±0.06 ppm of 2n, Cu, Co, Pb and Cd respetively. Mean Cu content in liver and forages samples were estimated as 4.84±0.62 and SS.40±1.56 ppm (wet basis) respectively. Based on clinical and laboratory, findings the problem of diarrhoea. ataxia and recumbency was diagnosed as enzootic ataxia due to primary copper deficiency. Therapeutic response to copper supplement further confirmed the diagnosis.